2006
DOI: 10.1097/01.meg.0000231753.58211.05
|View full text |Cite
|
Sign up to set email alerts
|

The gastric mucosa in gastric cancer patients in a low-incidence area

Abstract: A quarter of the patients had a normal stomach, and pyloric metaplasia was distinctly uncommon. Approaches to prevention and early detection of gastric cancer based on bioptic or serological demonstration of atrophy and metaplasia could overlook at least 25% of the people at risk in certain populations and may need to be adapted to local conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition, the observed diminishing OR for the intestinal type cancer in our regression model strengthens our suggestion. Another limitation of our study is that due to retrospective nature of our gastric cancer material and unreliability of resection specimens in the diagnosis of the infection (Genta and Pusztaszeri, ), we were not able to correlate the genotype frequencies with H. pylori infection in the cancer series. However, the importance of H. pylori in the pathogenesis of gastric cancer has been well documented, and in agreement with previous observations (Sipponen and Marshall, ), signs of chronic gastritis were present in majority (58/61; 96%) of gastric cancer patients.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the observed diminishing OR for the intestinal type cancer in our regression model strengthens our suggestion. Another limitation of our study is that due to retrospective nature of our gastric cancer material and unreliability of resection specimens in the diagnosis of the infection (Genta and Pusztaszeri, ), we were not able to correlate the genotype frequencies with H. pylori infection in the cancer series. However, the importance of H. pylori in the pathogenesis of gastric cancer has been well documented, and in agreement with previous observations (Sipponen and Marshall, ), signs of chronic gastritis were present in majority (58/61; 96%) of gastric cancer patients.…”
Section: Discussionmentioning
confidence: 98%
“…However, if there are features suggestive of a dropout of oxyntic glands, an immunohistochemical stain for gastrin‐producing cells (G cells) will be needed to establish the origin of each fragment (G cells, abundant in the antrum, are rare or absent from the oxyntic mucosa) and to determine whether corpus atrophy is present . Pepsinogen I staining, although not widely available in non‐specialised laboratories, is also a very specific tool to identify the atrophic corpus by highlighting the native oxyntic commitment of the pseudo‐pyloric metaplastic glands . However, these stains add considerable expense to the processing of a gastric biopsy set.…”
Section: Discussionmentioning
confidence: 99%
“…Three were classified as a mixed type. Other studies have also reported that cardia cancers are predominantly of intestinal type [14, 31], whereas ECL-cell-derived cancer developing in hypergastrinemic patients with pernicious anaemia are of the diffuse type [19]. …”
Section: Discussionmentioning
confidence: 99%